2021
DOI: 10.3390/atmos12121699
|View full text |Cite
|
Sign up to set email alerts
|

Is Hadley Cell Expanding?

Abstract: This review provides a comprehensive coverage of changes of the Hadley Cell extent and their impacts on the weather, climate, and society. The theories predicting the Hadley Cell width are introduced as a background for the understanding of the circulation changes and the metrics used for detection. A variety of metrics derived from various data sources have been used to quantify the Hadley Cell width. These metrics can be classified as dynamical, hydrological, thermal, and chemical metrics, based on the prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 173 publications
(413 reference statements)
2
9
0
Order By: Relevance
“…Moreover, as concluded in previous studies, the variations of HC are closely associated with the distribution of meridional structure of the tropic SST (Feng and Li, 2013;Guo and Tan, 2018;Sun et al, 2018). Different meridional structures of SST, like the asymmetric structure and symmetric structure along the equator, can generate great impacts on the HC at different temporal-spatial scales, indicating the response ratio of the asymmetric (symmetric) structure of the HC to asymmetric (symmetric) structure of SST varied with different thermal conditions (Feng et al, 2016;Xian et al, 2021).…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Moreover, as concluded in previous studies, the variations of HC are closely associated with the distribution of meridional structure of the tropic SST (Feng and Li, 2013;Guo and Tan, 2018;Sun et al, 2018). Different meridional structures of SST, like the asymmetric structure and symmetric structure along the equator, can generate great impacts on the HC at different temporal-spatial scales, indicating the response ratio of the asymmetric (symmetric) structure of the HC to asymmetric (symmetric) structure of SST varied with different thermal conditions (Feng et al, 2016;Xian et al, 2021).…”
Section: Introductionsupporting
confidence: 51%
“…In addition, the enhanced variations of HC in the boreal winter have also been ascribed to the strengthened asymmetric mode of ENSO during the last decades . Moreover, the possible impacts of SST warming on the HC variations have been studied, and it is found that the global SST warming is conducive to the enhancement of the predominant mode of the HC's seasonal variability (Zhou and Wang, 2006;Ma and Li, 2008;Zhou et al, 2020;Xian et al, 2021). Meanwhile, the variations of thermal conditions over the IPWP also greatly impact the connection between the HC and the tropic SST, especially after 1980 (Feng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There are several metrics to quantitively analyze the Hadley cell, its edge and its circulation strenght. We choose to use the average meridional streamfunction Ψ (Xian et al, 2021) to quantify its intensity, which is defined as :…”
Section: Meridional Streamfunctionmentioning
confidence: 99%
“…There are several metrics to quantitively analyze the Hadley cell, its edge and its circulation. We choose to use the average meridional streamfunction Ψ (Xian et al, 2021) to quantify its intensity, which is defined as :…”
Section: Meridional Streamfunctionmentioning
confidence: 99%